PIROLISIS SABUN LOGAM DARI ASAM OLEAT UNTUK PRODUKSI BIOHIDROKARBON HIJAU - Hernowo, Pandit; Arumsari, Alif Gita; Aliyah, Ayang Hisna Zainatul; Njurumana, Violica Celloce; Patimah , Siti (Department of Agroindustrial Technology, Bogor Agricultural University, 2024)
Metal soap pyrolysis is an attractive route for green gasoline fuel production because it is a straightforward process with no hydrogen supply needed and is operated under a pressure atmosphere. Pyrolysis of soap made from oleic acid is carried out via the catalytic route in a Py-GC reactor. Bivalent metals such as Zn, are evaluated as catalysts in pyrolysis. The preparation of a mixture of oleic acid: NaOH: Zn metal was studied at a concentration of 1:1:1. Thermal stability analysis of pyrolysis was studied at a temperature of 250oC with a heating rate of 10, 20, 40oC/min. This research aimed to figure out the characteristics of the relationship between raw materials, metal soap, and the bio-hydrocarbon products produced. Experimental results show that Zn metal can supply good temperature stability during the pyrolysis heat degradation process. Zn metal also can act as a catalyst, helping the decarboxylation reaction of oleic acid to become short-chain bio-hydrocarbons. The yield of short-chain bio-hydrocarbons C9-C18 was 0.04-7.33%w/w, meanwhile, long-chain bio-hydrocarbons reached 48.07%w/w. The presence of oxygenate compounds is due to the low quality of the raw materials. A decrease in the quality of raw materials can be caused by poor handling and storage of oleic acid as evaluated by large saponification, acid, and peroxide numbers. Keywords : biohydrocarbons, oleic acid, metal soap, pyrolysis, TGA